2008
DOI: 10.1136/bjsm.2008.053272
|View full text |Cite
|
Sign up to set email alerts
|

Is tai chi beneficial for improving aerobic capacity? A systematic review

Abstract: Tai chi has been claimed to generate beneficial effects with respect to a wide range of diseases. The purpose of this systematic review was to evaluate evidence from randomised clinical trials (RCTs) testing the effectiveness of tai chi for increasing aerobic capacity. Systematic searches were conducted on 14 electronic databases without restrictions on population characteristics or the language of publication. The outcome measures considered for inclusion were changes in maximal oxygen consumption as a test f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…Seven SRs concluded that the current data were insufficient to draw firm conclusions,8 10 21 25 29 32 37 eight SRs concluded that t'ai chi did not have a beneficial effect,5 6 13 14 17 20 24 26 and 20 SRs concluded that t'ai chi might be effective 7 8 11 12 15 16 18 19 22 23 27 28 30 31 3336 38 39. Of the nine high-quality SRs,5 9 11 13 14 17 21 24 32 one arrived at a positive conclusion,11 five arrived at a negative conclusion,5 13 14 17 24 and in three SRs,9 21 32 no clear conclusions were drawn.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Seven SRs concluded that the current data were insufficient to draw firm conclusions,8 10 21 25 29 32 37 eight SRs concluded that t'ai chi did not have a beneficial effect,5 6 13 14 17 20 24 26 and 20 SRs concluded that t'ai chi might be effective 7 8 11 12 15 16 18 19 22 23 27 28 30 31 3336 38 39. Of the nine high-quality SRs,5 9 11 13 14 17 21 24 32 one arrived at a positive conclusion,11 five arrived at a negative conclusion,5 13 14 17 24 and in three SRs,9 21 32 no clear conclusions were drawn.…”
Section: Resultsmentioning
confidence: 98%
“…The first authors originated from the USA (n=10), the UK (n=9), Korea (n=6), France (n=2), Australia (n=2), Netherlands (n=2), Canada (n=1), New Zealand (n=1), Singapore (n=1) and Sweden (n=1). Ten reviews incorporated a meta-analytic approach 5 11 14 17 18 20 21 24 27 32. The reviews were based on two to 47 primary studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis result also demonstrated that t'ai chi was not more beneficial for improving aerobic capacity in healthy or sick people than other physical exercises. 31 Therefore, it is necessary to conduct trials with larger sample sizes and higher methodological quality to detect any advantages that TCQ might demonstrate for improvement in physical capacity compared with other exercise trainings in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence show that the exercises involving stretching exercise incorporate with breathing practice such as Yoga and Taichi (Madanmohan et al, 2008;Wang, 2008) provide physical health benefit including cardiorespiratory function, muscle strength and posture control (Lee et al, 2009;Tran et al, 2001;Tsang and Hui-Chan, 2004). Moreover, they can also enhance antioxidant enzymes activities such as Superoxide Dismutase (SOD) and Glutathione Peroxidase (GSH-Px) while decrease Malondialdehyde (MDA) level (Agte et al, 2011;Hegde et al, 2011;Goon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%